2003
DOI: 10.1016/s0028-3932(02)00143-4
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of feeling sympathy

Abstract: Positron emission tomography (PET) was used to investigate the neural correlates of feeling sympathy for someone else (i.e. the affinity, association, or relationship between persons wherein whatever affects one similarly affects the other). While undergoing PET scans, subjects were presented with a series of video-clips showing individuals (who were semi-professional stage actors) telling sad and neutral stories, as if they had personally experienced them. These stories were told with either congruent or inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
132
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(142 citation statements)
references
References 74 publications
6
132
0
4
Order By: Relevance
“…For example, the activation in this study was in pre-SMA and previous research found anterior SMA activity to be associated with grasp observation and imitation and posterior SMA activity with grasp performance (Grafton et al, 1996a). Tasks where the subject must take the perspective of the object have found consistent engagement of right inferior parietal (thought to suppress the subject's own perspective) and medial prefrontal and frontal pole (thought to inhibit the subject's self-processes) (Decety & Chaminade, 2003;Decety et al, 2002;Ruby & Decety, 2001). In a task where objects directed their emotion toward the subject (as opposed to away from the subject), the anterior portion of the superior temporal lobe was selectively activated (Wicker et al, 2003b).…”
Section: Recent Neuroscientific Evidencesupporting
confidence: 65%
See 2 more Smart Citations
“…For example, the activation in this study was in pre-SMA and previous research found anterior SMA activity to be associated with grasp observation and imitation and posterior SMA activity with grasp performance (Grafton et al, 1996a). Tasks where the subject must take the perspective of the object have found consistent engagement of right inferior parietal (thought to suppress the subject's own perspective) and medial prefrontal and frontal pole (thought to inhibit the subject's self-processes) (Decety & Chaminade, 2003;Decety et al, 2002;Ruby & Decety, 2001). In a task where objects directed their emotion toward the subject (as opposed to away from the subject), the anterior portion of the superior temporal lobe was selectively activated (Wicker et al, 2003b).…”
Section: Recent Neuroscientific Evidencesupporting
confidence: 65%
“…In this cognitive form of empathy, subjects could take the spatial perspective of the object (as proposed by perspective-taking models of empathy, e.g. Decety & Chaminade, 2003), but more often subjects probably just imagine themselves to be the object. In this process, the orbitofrontal cortex is needed as a 'convergence/divergence zone', to link the constructed feeling state of the object with an appropriate response (Bechara et al, 2000).…”
Section: Automaticallymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the left IFG was also found to be involved with semantic, syntactic, and phonological processes that are relevant to both the production and comprehension of speech (41). These processes include semantic retrieval (60), lexical decision (61), syntactic transformations (62,63), and verbal working memory (64)(65)(66)(67)(68)(69). Based on such reports it was argued that the left IFG is involved with both production and comprehension processes (21,70,71).…”
Section: Discussionmentioning
confidence: 99%
“…However, the existence of areas exclusively devoted to language has increasingly been challenged by experimental evidence showing that Broca's area and its homologue in the right hemisphere also become active during the observation of hand/mouth actions performed by other individuals (Aziz-Zadeh, Koski, Zaidel, Mazziotta, & Iacoboni, 2006;Decety et al, 1997;Decety & Chaminade, 2003;Grafton, Arbib, Fadiga, & Rizzolatti, 1996;Grè zes, Costes, & Decety, 1998;Grè zes, Armony, Rowe, & Passingham, 2003;Iacoboni, Woods, Brass, Bekkering, Mazziotta, & Rizzolatti, 1999;. This finding seems to favor the evolutionary hypothesis, supporting the idea that the linguistic processing that characterizes Broca's area may be closely related to gesture processing.…”
Section: Introductionmentioning
confidence: 90%